(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The family is a social unit that provides economic support, socialization, and emotional and psychological care for its members. However, modernization and the effects of the Industrial Revolution have made families increasingly vulnerable and crisis-prone. In the past, families were largely self-sufficient, producing most of what they consumed. The extended family structure, where each member had specific roles, was predominant, and marriage was considered permanent, with the father as the head. However, modernization has shifted family dynamics, reducing its economic-productive role and promoting individualism, where personal desires take precedence over family needs. Mate selection is now based on personal preference rather than family interests, and divorce rates have risen. Women increasingly serve as breadwinners, contributing to unstable family structures, rising numbers of street children, mental health issues, and elder neglect. This paper examines the role of social workers in mitigating these challenges and promoting family stability amid changing societal norms and values.